Experimental studies using OMV in a new platform of SARS-CoV-2 vaccines - Emanuelle B. Gaspar; Carlos Roberto Prudencio; Elizabeth De Gaspari (Taylor & Francis Group, 2021)
Although COVID-19 vaccines have recently been approved for emergency use, search for new vaccines are still urgent, since the access of the countries, especially the poorest, to the vaccines, has shown to be slower than the necessary to rapidly control the pandemic. We proposed a novel platform for vaccine using recombinant receptor binding domain (rRBD) from Sars-Cov-2 spike protein and Neisseria meningitidis outer membrane vesicles (OMVs). The antigen preparation produced a humoral and cellular immune response. Taken together our findings suggest a good immunostimulatory patter in response to immunization with rRBD plus N. meningitidis OMV.